Nanostructured core–shell metal borides–oxides as highly efficient electrocatalysts for photoelectrochemical water oxidation. Issue 5 (22nd January 2020) - Lu, Can; Jothi, Palani R.; Thersleff, Thomas; Budnyak, Tetyana M.; Rokicinska, Anna; Yubuta, Kunio; Dronskowski, Richard; Kuśtrowski, Piotr; Fokwa, Boniface P. T.; Slabon, Adam
Abstract : 2D CoB nanosheets and FeB nanoplates were employed as catalysts for WO3 photoanodes. The functionalized photoanodes present meaningfully improved PEC water oxidation performances, exceeding Co-Bi - and Co(OH) x -modified WO3 photoanodes. Abstract : Oxygen evolution reaction (OER) catalysts are critical components of photoanodes for photoelectrochemical (PEC) water oxidation. Herein, nanostructured metal boride MB (M = Co, Fe) electrocatalysts, which have been synthesized by a Sn/SnCl2 redox assisted solid-state method, were integrated with WO3 thin films to build heterojunction photoanodes. As-obtained MB modified WO3 photoanodes exhibit enhanced charge carrier transport, amended separation of photogenerated electrons and holes, prolonged hole lifetime and increased charge carrier density. Surface modification of CoB and FeB significantly enhances the photocurrent density of WO3 photoanodes from 0.53 to 0.83 and 0.85 mA cm −2, respectively, in transient chronoamperometry (CA) at 1.23 V vs. RHE (VRHE ) under interrupted illumination in 0.1 M Na2 SO4 electrolyte (pH 7), corresponding to an increase of 1.6 relative to pristine WO3 . In contrast, the pristine MB thin film electrodes do not produce noticeable photocurrent during water oxidation. The metal boride catalysts transform in situ to a core–shell structure with a metal boride core and a metal oxide (MO, M = Co, Fe) surface layer. When coupled to WO3 thin films, the CoB@CoO x nanostructures exhibit a higher catalytic enhancement than corresponding pure cobalt borate (Co-Bi ) and cobalt hydroxide (Co(OH) x ) electrocatalysts. Our results emphasize the role of the semiconductor–electrocatalyst interface for photoelectrodes and their high dependency on materials combination.